Association Between Hyponatremia and Maintenance Intravenous Solutions in Critically Ill Children: A Retrospective Observational Study - Fernández-Sarmiento, Jaime; Pérez, Andrea; Echeverri, Maria Alejandra; Jimenez, Paola; Joachim, Maria Alejandra; Andrés-Jagua, (Frontiers in Pediatrics, 2021)
Objetive: We sought to determine the association between maintenance intravenous solutions and the presence of hyponatremia in children in pediatric intensive care (PICU). Materials and Methods: An analytical observational study in children hospitalized in the PICU between January 2015 and December 2018. Patients who received maintenance fluids within the first 48 h after admission and who had at least two serum sodium levels drawn during this time were included. Measurements and Main Results: A total of 1,668 patients were admitted to the PICU during the study period, 503 of whom met the inclusion criteria. The median age was 24 months (IQR 8–96) and 50.9% were female. Altogether, 24.1% of the children developed hyponatremia; it was more frequent in those who received hypotonic solutions (63 vs. 37%; OR 1.41 95% CI 0.92, 2.15 p = 0.106), who also had a longer hospital stay (20 vs. 14 days, difference in means 8 days, 95% CI 2.67, 13.3, p = 0.001). Children who received loop diuretics and those who were post-operative had a greater risk of developing hyponatremia if they received hypotonic solutions (aOR 2.1 95% CI 1.41, 3.0, p = 0.000). Those with balanced isotonic solutions had a lower risk of developing hyponatremia (aOR 0.59 95% CI 0.35, 0.99, p = 0.004) and hyperchloremia (aOR 0.51 95% CI 0.34, 0.77, p = 0.000), adjusted for disease severity. A greater risk of death was found in the group with severe hyponatremia <130 mEq/L (aOR 9.75 95% CI 1.64–58.15; p = 0.01). Conclusions: Hyponatremia associated with the use of hypotonic maintenance solutions occurs in one out of four children in intensive care. The use of these solutions is associated with a longer hospital stay, and the main risk groups are post-operative patients and those who receive loop diuretics. Clinical studies are needed to determine which maintenance solutions have the greatest efficacy and safety in critically ill children.